Penentuan Kesepadanan Pasangan Pernikahan Berdasarkan Perhitungan Weton - Dwi Arini Zubaidah (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2019)
This article is intended to answer the factors of weton calculation practice in Ngaringan and sociological analysis of these practices. This article uses field research by observing, interviewing and documenting as well as using Max Weber's theory of social action. This article concludes that the concept of comparability already exists in the rules of Islamic law, positive law and customary law. Therefore, the existence of the traditional Weton calculation practiced by the Ngaringan Grobogan community in Central Java has several factors: first, adat and belief. The community preserves the calculation of weton as a custom originating from ancestors. Second, the form of preventive business. Third, a form of respect for both parents. The traditional Weton calculation practiced by the Ngaringan community is a social action in the traditional action category. The Ngaringan people still maintain the custom of Weton calculation even though the custom is not regulated in a written rule.